Sustained virologic suppression with abacavir, emtricitabine, and crushed dolutegravir and tenofovir alafenamide in a patient with HIV and eosinophilic esophagitis. (March 2020) - Moore, Sarah E; Huesgen, Emily; Howe, Zachary
We report the use of crushed dolutegravir (DTG) and tenofovir alafenamide (TAF) tablets in a 27-year-old man with progressive dysphagia due to eosinophilic esophagitis, which severely limited compliance, leading to viral resistance. Based on his drug resistance history, allergies, and inability to swallow tablets intact, he was transitioned to DTG 50 mg (crushed), TAF 25 mg (crushed), liquid abacavir (20 mg/ml) 30 ml, and liquid emtricitabine (10 mg/ml) 24 ml orally daily. After receiving this regimen for five months, the patient's HIV viral load decreased from 9910 to 59 copies/ml and after ten total months became suppressed at <20 copies/ml. Our case report suggests administration of crushed DTG and TAF tablets may be a viable option for patients with dysphagia and limited treatment options.